Caloric Restriction Mimetic 2-Deoxyglucose Alleviated Inflammatory Lung Injury via Suppressing Nuclear Pyruvate Kinase M2–Signal Transducer and Activator of Transcription 3 Pathway - Hu, Kai; Yang, Yongqiang; Lin, Ling; Ai, Qing; Dai, Jie; Fan, Kerui; Ge, Pu; Jiang, Rong; Wan, Jingyuan; Zhang, Li (Frontiers in Immunology, 2018)
Inflammation is an energy-intensive process and caloric restriction (CR) could provide anti-inflammatory benefits. CR mimetics (CRM), such as the glycolytic inhibitor 2-deoxyglucose (2-DG), mimic the beneficial effects of CR without inducing CR-related physiologic disturbance. This study investigated the potential anti-inflammatory benefits of 2-DG and the underlying mechanisms in mice with lipopolysaccharide (LPS)-induced lethal endotoxemia. The results indicated that pretreatment with 2-DG suppressed LPS-induced elevation of tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6). It also suppressed the upregulation of myeloperoxidase (MPO), attenuated Evans blue leakage, alleviated histological abnormalities in lung and improved the survival of LPS-challenged mice. Treatment with 2-DG had no obvious effects on the total level of pyruvate kinase M2 (PKM2) but it significantly suppressed LPS-induced elevation of PKM2 in the nuclei. Prevention of PKM2 nuclear accumulation by ML265 mimicked the anti-inflammatory benefits of 2-DG. In addition, treatment with 2-DG or ML265 suppressed the phosphorylation of nuclear signal transducer and activator of transcription 3 (STAT3). Inhibition of STAT3 by stattic suppressed LPS-induced inflammatory injury. Interestingly, post-treatment with 2-DG at the early stage post LPS chanllenge also improved the survival of the experimental animals. The present study found that treatment with 2-DG, a representative CRM, provided anti-inflammatory benefits in lethal inflammation. The underlying mechanisms included suppressed nuclear PKM2-STAT3 pathway. These data suggests that 2-DG might have potential value in the early intervention of lethal inflammation.